Convergence of detrital stoichiometry predicts thresholds of nutrient‐stimulated breakdown in streams. Issue 6 (2nd September 2016) - Manning, David W. P.; Rosemond, Amy D.; Gulis, Vladislav; Benstead, Jonathan P.; Kominoski, John S.; Maerz, John C.
Abstract: Nutrient enrichment of detritus‐based streams increases detrital resource quality for consumers and stimulates breakdown rates of particulate organic carbon (C). The relative importance of dissolved inorganic nitrogen (N) vs. phosphorus (P) for detrital quality and their effects on microbial‐ vs. detritivore‐mediated detrital breakdown are poorly understood. We tested effects of experimental N and P additions on detrital stoichiometry (C:N, C:P) and total and microbial breakdown (i.e., with and without detritivorous shredders, respectively) of five detritus types (four leaf litter species and wood) with different initial C : nutrient content. We enriched five headwater streams continuously for two years at different relative availabilities of N and P and compared breakdown rates and detrital stoichiometry to pretreatment conditions. Total breakdown rates increased with nutrient enrichment and were predicted by altered detrital stoichiometry. Streamwater N and P, fungal biomass, and their interactions affected stoichiometry of detritus. Streamwater N and P decreased detrital C:N, whereas streamwater P had stronger negative effects on detrital C:P. Nutrient addition and fungal biomass reduced C:N by 70% and C:P by 83% on average after conditioning, compared to only 26% for C:N and 10% for C:P under pretreatment conditions. Detritus with lowest initial nutrient content changed the most and had greatest increases in total breakdown rates. Detrital stoichiometry was reduced and differences among detritus types were homogenized by nutrient enrichment. With enrichment, detrital nutrient content approached detritivore nutritional requirements and stimulated greater detritivore vs. microbial litter breakdown. We used breakpoint regression to estimate values of detrital stoichiometry that can potentially be used to indicate elevated breakdown rates. Breakpoint ratios for total breakdown were 41 (C:N) and 1518 (C:P), coinciding with total breakdown rates that were ~1.9 times higher when C:N or C:P fell below these breakpoints. Microbial and shredder‐mediated breakdown rates both increased when C:N and C:P were reduced, suggesting that detrital stoichiometry is useful for predicting litter breakdown dominated by either microbial or shredder activity. Our results show strong effects of nutrient enrichment on detrital stoichiometry and offer a robust link between a potential holistic nutrient loading metric (decreased and homogenized detrital stoichiometry) and increased C loss from stream ecosystems.